HIGH PRESSURE EQUILIBRIUM OF NICKEL AND COBALT BETWEEN METAL AND MANTLE MINERALS - IMPLICATIONS FOR CORE-MANTLE EQUILIBRIUM - Malavergne V.; Guyot F.; Peyronneau J.; Poirier J.P. (My University, 1999)
In order to test the effect of very high pressures on the siderophile behaviour of two elements, Ni and Co, we have carried out diamond anvil cell experiments on Ni- and Co-bearing systems, up to 70 GPa. Observation of recovered samples by analytical transmission electron microscopy shows that Ni and Co remain siderophile at least up to 70 GPa, but that their siderophile character decreases with pressure, as already observed in previous studies at lower pressures. Our results also suggest that the abundances of Ni and Co observed in the Earth's upper mantle cannot be explained by very high pressure equilibrium between silicate perovskite, magnesiowustite, and metal.